Caracterização dos acidentes envolvendo tratores agrícolas nas rodovias federais brasileiras - Macedo, Deivielison Ximenes Siqueira (2014)
The use of tractors in agriculture intensifies every year in Brazil. Currently their use is critical in various activities whether in rural areas (soil preparation, planting, cultural and harvest treatment), whether in the urban environment (resurfacing of roads and earthworks). However, the intensified use of the tractor, has corroborated the occurrence of accidents caused by improper use of the machine, how to operate without knowing her or disrespect your boundaries. Accidents with tractors is a global problem, however in Brazil still does not give due importance to this issue, when compared with other subjects in the area of machines (tests, reviews of equipment, etc.). The knowledge about the conditions under which an accident occurred is necessary to try to prevent or reduce the frequency with which it occurs again, so there is a need to characterize the accident with tractors. Given this reality, the present study aimed to characterize accidents with tractors in the Brazilian federal highways in the period 2008 to September 2011, identifying the main types and causes of accidents, time of day, age of injured operators and highways that had more accidents. The records were obtained by the Bulletin of Traffic Accidents (BAT), obtained through an agreement with the Sixteenth Regional Superintendence of the Federal Highway Police in Fortaleza. In BAT is information such as: type of accident, the cause of the accident, the highway where the accident occurred, the age of the victim and the time of the accident and other information. From this information the application of methods of descriptive statistics for the data relating to accidents in Brazil was performed, the data were grouped into classes, later the absolute frequencies were transformed into relative frequencies to better represent them. From the results it was concluded that the collisions were responsible for approximately 82% of accidents, with the rear-end collision the main type of collision with 33.81% of the accidents in Brazil. Inattention was the main cause of accidents with 62.77%, the majority of accidents occurred in the afternoon with 37.12%. The age group with the highest frequency of accidents was the range between 25-30 years with 16.03% and highway accidents was more BR -101 with 14.94 % of domestic accidents in total length. The large majority of accidents occurred in good weather with good visibility on highways in good repair and however due to lack of attention and there are numerous explanations for this occurrence, one possibility is the difference in speed between the tractor and the other vehicles.